2022 IFPRI annual report - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
IFPRI’s 2022 Annual Report presents highlights from our research work in low- and middle-income countries and on global challenges. In 2022, IFPRI provided critical analysis on the food systems impact of the Russia-Ukraine war and related food, fertilizer, and fuel price crisis, as well as the ongoing COVID-19 pandemic. Work in our strategic research areas—climate resilience and sustainability, healthy diets and nutrition, inclusive and efficient food systems, institutions and governance, and rural transformation, as well as cross-cutting work on gender—continued to inform policies and programs to end hunger and malnutrition sustainably at both national and global levels.